Rapid Electrochemical Detection of Radiolysis Products in an Aqueous Solution Exposed to Alpha Particle Beams - J. E. Liedhegner; W. Jennings; J. Wainright (International Journal of Electrochemistry, 2011)
An electrochemical cell has been developed that allows for the rapid and exhaustive detection of oxygen and/or hydrogen peroxide produced during the radiolysis of aqueous solutions by alpha particle or proton beams. Short, 10–100 s, exposures were sufficient to yield steady-state electrochemical currents proportional to the radiolysis G-factor. The use of thin SiC windows provided a robust means of separating the vacuum environment of the ion-beam accelerator from the aqueous solution at atmospheric pressure with minimal energy loss.